Errors in Islamic Calligraphy: A Short Analytical and Critical Evaluation - Muhammad Asad Latif (Penerbit Hellow Pustaka, 2024)
The idea of undermining the familiar is to challenge the constants and its acknowledged limitations, in contrast to deconstruction and its destructive pursuit. It is accomplished by means of the reception process and the constraints imposed by the way a word or text is formed, as well as by the overall structural and design framework and, specifically, by Arabic calligraphy. This depends on how the dual phenomena and the content's presentation are understood and interpreted by the recipient. More precisely, its expressive phenomenology reveals its actuality; four chapters of research were devoted to the study of